Two cases with pycnodysostosis in a family: a case report - Reddy, K. Venkataramana; Soren, Chapay; Geethika, M.; Malathi, V. (International Journal of Contemporary Pediatrics, 2020)
Pycnodysostosis (Greek, pycnos - density, dys - defect, ostosis - bone) is a rare inherited disorder of the bone, first described by Maroteaux and Lamy. Pycnodysostosis is an autosomal recessive disorder, with incidence estimated to be 1.7 per 1 million births. Clinical presentation of this disorder include short stature, dolichocephalic skull, frontal bossing, obtuse mandibular angle, dysplastic clavicles, and short hands and feet, diffuse osteosclerosis, acro-osteolysis along with the finger and nail abnormalities. The main oral aspects are midfacial hypoplasia, a grooved palate, and dental abnormalities include double row of teeth, delayed eruption of permanent dentition, multiple caries. Pathological fractures of the bones occur due to sclerosis. Radiologically, skull bones appear thickened with open fontanels which look like ‘lakes of bones’, hypoplasia of facial bones, generalized osteosclerosis, open fontanels and cranial sutures, non pneumotization of paranasal sinuses, and fractures commonly in lower limbs.